Epileptic Spasms: Evidence for oral corticosteroids and implications for low and middle income countries (Systematic Review) - Raga, Sharika Vinod (University of Cape Town, 2020)
Implementation of international guidelines for the treatment of epileptic spasms, is challenging when access to adrenocorticotrophic hormone (ACTH) and vigabatrin is restricted, especially in Low and Middle Income Countries (LMIC). Oral corticosteroids are alternative interventions but evidence for the optimal agent, dose, duration, efficacy and long-term effects are lacking. A systematic review of the literature was performed to assess the quality of evidence of prednisone and prednisolone (oral corticosteroids) for the management of epileptic spasms. There is level C recommendation based on class III evidence to support the efficacy of oral corticosteroids for the acute clinical control of epileptic spasms and EEG resolution. Efficacy of oral corticosteroids in comparison to the internationally recommended intervention of ACTH has class IV evidence supporting level U recommendation. Similarly, there is no data on the risk of relapse with oral corticosteroids (class IV, level U), compared to ACTH. There is class IV evidence supporting level U recommendation for the safety of oral corticosteroids and class II evidence for level B recommendation for ACTH. In terms of oral corticosteroids and effects on long-term development there is class IV evidence leading to level U recommendation, compared to class III evidence supporting level C recommendation for ACTH. Randomized controlled studies are needed to compare oral corticosteroids with ACTH, the optimal dosage and regimen as well as the long-term neurodevelopmental outcomes. Based on the limited existing studies a treatment guideline for LMIC is proposed which could be used to standardize interventions permitting clarification of these unmet questions.